2006
DOI: 10.1161/01.res.0000244015.10655.3f
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Mediates Angiotensin II–Induced Phospho-Ser536 Nuclear Factor κB/RelA Subunit Exchange on the Interleukin-6 Promoter in VSMCs

Abstract: Abstract-The vasoconstrictor angiotensin II (Ang II) accelerates atherosclerosis by inducing vascular gene expression programs, producing monocyte recruitment, and vascular remodeling. In vascular smooth muscle cells (VSMCs), Ang II signaling activates interleukin (IL)-6 expression, a cytokine producing acute-phase inflammation, mediated by the transcription factor nuclear factor B (NF-B). The classical NF-B activation pathway involves cytoplasmic-to-nuclear translocation of the potent RelA transactivating sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 40 publications
4
58
0
1
Order By: Relevance
“…These studies showed that Ang II induces NF-κB /RelA activation in VSMCs by increasing the relative abundance of phospho-Ser-536 RelA in the nucleoplasmic pool. We also confirmed Ang II-induced enhanced phospho-Ser-536 RelA formation in rat aortas treated with Ang II, establishing relevance to vascular signaling in vivo (Choudhary, et al, 2007;Cui, et al, 2006). Our group further showed that Ang II-induced RelA Ser-536 phosphorylation is mediated by NF-κB-inducing kinase (NIK), the major regulated step controlling non-canonical NF-κB signaling.…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcssupporting
confidence: 69%
See 1 more Smart Citation
“…These studies showed that Ang II induces NF-κB /RelA activation in VSMCs by increasing the relative abundance of phospho-Ser-536 RelA in the nucleoplasmic pool. We also confirmed Ang II-induced enhanced phospho-Ser-536 RelA formation in rat aortas treated with Ang II, establishing relevance to vascular signaling in vivo (Choudhary, et al, 2007;Cui, et al, 2006). Our group further showed that Ang II-induced RelA Ser-536 phosphorylation is mediated by NF-κB-inducing kinase (NIK), the major regulated step controlling non-canonical NF-κB signaling.…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcssupporting
confidence: 69%
“…Interestingly, we also found that phospho-Ser-536 RelA formation was blocked by RhoA inhibition, suggesting that Ser-536 phosphorylation was mediated upstream by RhoA. In addition, RhoA inhibition also blocked Ang II-induced IL-6 expression, indicating that Ang II-inducible phospho-Ser-536 RelA was required for IL-6 activation (Cui, et al, 2006). Our studies in Ang II-stimulated VSMCs further showed that total RelA binding did not change on the native IL-6 promoter in response to Ang II, but fractional binding of phospho-Ser-536 RelA to the IL-6 promoter was increased (Choudhary, et al, 2007).…”
Section: Mechanism Of Nf-κb Activation By Ang II In Vsmcsmentioning
confidence: 51%
“…This phenomenon has been experimentally verified by us using Ang II, a ligand that activates phosphoSer 536 RelA formation without affecting total RelA nuclear abundance. In this case, an increase in the fraction of nuclear phospho-Ser 536 RelA can rapidly exchange with promoterbound hypophosphorylated RelA, producing a transition in gene expression from an inactive state to an activated one (14). Our ChIP analysis of phospho-Ser 276 RelA binding, however, indicates that this isoform does not rapidly exchange with the hypophosphorylated RelA bound to the Naf1 gene.…”
mentioning
confidence: 69%
“…It is known that several pro-inflammatory stimuli, such as TNFα, UV light, and LPS, induce phosphorylation of p65 at the Ser 536 residue, which is triggered by IKKαβ phosphorylation in the cytoplasm. Recent studies indicate that Ang II also activates NF-κB through the phosphorylation of p65 at Ser 536, which is shown to be mediated by IKKαβ phosphorylation in various cellular models (Cui et al 2006;Douillette et al 2006;Wei et al 2008). However, these findings are in contrast to earlier findings on TNFα showing Ser 276 phosphorylation by mitogenand stress-activated protein kinase-1 (MSK-1) in the nucleus (Viatour et al 2005;Zhong et al 2002).…”
Section: Introductionmentioning
confidence: 99%